The THE INFLUENCE OF PRICE AND QUALITY OF PRODUCTS ON CUSTOMER SATISFACTION IN PT. RAMAYANA LESTARI SENTOSA - ferdinand napitupulu (Akuntansi Prima, 2019)
Tight competition where more and more producers are involved in meeting customer needs and desires, companies need to increase customer satisfaction by providing relatively cheap prices and providing quality products. The formulation of the problem in this study is whether the price and quality of products in a simultaneous manner affect customer satisfaction at PT. Ramayana Lestari Sentosa. This Research Hypothesis is the price and product quality Simultaneously affect customer satisfaction at PT. Ramayana Lestari Sentosa. Data collection techniques were carried out by distributing questionnaires and documentation techniques and data analysis methods using multiple linear regression analysis. The population in this study were all customers at PT. Ramayana Lestari Sentosa who bought 184 products. The sampling used in this study using Slovin formula, so the number of samples of this study were 65 people. The results of the multiple linear regression equation research in this study are Y = 1,503 + 0,568 X1 + 0,510X2.. The results showed that the price variable (X1) and product quality (X2) were positive for customer satisfaction (Y). This shows the price and quality of products can have an effect on increasing customer satisfaction. Partially shows that Price has a positive and significant effect on customer satisfaction. Partial test results show that product quality has a positive and significant effect on customer satisfaction. Simultaneous test results show that product prices and quality have a positive and significant effect on customer satisfaction at PT. Ramayana Lestari Sentosa and the coefficient of determination is 84.7% and the remaining 15.3% is explained by independent variables that are not examined. It is expected that PT. Ramayana Lestari Sentosa must further improve the performance of the company by striving that the price offered must be in accordance with market demand and the quality of the product and always provide the best products to customers by offering quality products to customers. Keywords: price, product quality and customer satisfaction